COMPENSATORY STRATEGIES FOR DYSGRAPHIC STUDENTS AT PRIMARY SCHOOL LEVEL (International Journal of Food and Nutritional Sciences, 2021)
The Purpose of this study is to test the effectiveness of compensatory strategies for Dysgraphia students at primary school level, for this researcher used experimental methodology with pre-test, post- test quasi experimental design. The investigator selects 60 IED students from primary level students through stratified sample techniques. These students further divided into two equal groups. First group selected as control group and second group as experimental group for the present study. This study finds out that The obtained value of Fy is 8.82, which is significant at 0.01 levels. So it can be concluded compensatory strategies are effective for dysgraphic students in primary school students compared to the prevailing method. The difference between the adjusted mean of the post test scores of the students in the experimental and control group were tested for significance. And it differ significantly The difference between the adjusted Y means indicated that the students in the experimental group significantly in their development in the post test. From the results it can be interpreted that compensatory strategies are effective for dysgraphia students in primary school students.